Session IV: Fair Use and Other Exceptions - McCoy, Stan (The Columbia Journal of Law & the Arts, 2017)
These remarks are a transcript of a talk that was given on October 14, 2016, at the Kernochan Center Annual Symposium at Columbia Law School. Session IV focused on efforts to incorporate exceptions into international copyright treaties and trade agreements, including for example, a flexible “fair use”-type exception. Session Panelists: Jonathan Band, Jonathan Band PLLC David Carson, Senior Counsel and Head of Copyright Policy Team, Office for Policy & International Affairs, U.S. Patent and Trademark OfficeU.S. Patent and Trademark Office Lital Helman, Professor, Ono Academic College Faculty of Law Stan McCoy, President and Managing Director of the Motion Picture Association (MPA) EMEA